Geologic and petrologic evidence for granulite facies partial melting in the Garies-Platbakkies supracrustal gneiss belt, Namaqualand metamorphic complex, South Africa - Baars, Franciscus Jacobus; Baars, Franciscus Jacobus (Department of Geological Sciences, 2017)
The Namaqua Province of southwestern Africa is comprised of a number of distinct tectonostratigraphic subprovinces and terranes, which have in common a 1100-1200Ma structural and metamorphic imprint. In the western Bushmanland Subprovince, E-Wtrending belts of supracrustal gneisses are intruded by and infolded with granitic gneisses of varying ages. A central zone of rocks metamorphosed in the granulite facies is bordered to the north and south by amphibolite facies rocks. A portion of the Garies-Platbakkies supracrustal gneiss belt has been mapped on a 1:15 000 scale. The supracrustal succession was deposited on an unconfirmed basement. It is structurally juxtaposed and infolded with three different granitic augen gneisses. Large bodies of orthopyroxene-bearing granite are syntectonically emplaced in the succession. A wide variety of anatectic granites crop out as sills, dykes and pods varying in size between a few metres and a few hundred metres. These bodies commonly truncate pre-existing foliations. The metamorphosed supracrustal succession contains gneissic equivalents of felsic, mafic and intermediate volanics; pelitic, semi-pelitic, magnesian and granitic composition sediments; feldspathic quartzites; and subordinate quartzites, banded iron formation and calc-silicates. The mineral assemblages of all the rocks indicate metamorphism in the granulite facies. A variety of field evidence exists which suggests that the metamorphic peak was responsible for generating significant quantities of partial melt. The rocks of the study area contain an early Dl fabric. This is refolded in tight, E-plunging D2 crenulation folds. D2 mineral fabrics pre-date the metamorphic peak. D3 open, asymmetric folds are N-vergent and fold the crystalline products partial melting. The southern limbs of D3-folds are attenuated in 04 shear zones. The whole belt is cut by steep, N-S-trending faults. A wide variety of thermobarometers are tested for their applicability to mineral assemblages in the supracrustal rocks. The results of this application suggest that the metamorphic peak occurred at 780 ± 30°C and 5.0 ± 0.4 kbar. Assemblages in shear zones indicate an isobaric retrograde cooling path. The phase relations of melting near the solidus are reviewed with reference to common assemblages in the leucosomes of rocks with granitic and peraluminous bulk compositions. Isobaric T-a(H₂O) sections are constructed from available experimental and thermochemical data. Biotite dehydration and dehydration melting reactions are balanced using natural mineral compositions. The predicted results are compared with the modal abundances of natural product assemblages. The results suggest that dehydration melting was responsible for migmatization, and the consequent reduction of water activity. The amount of melt produced was controlled by the amount of water available from the dehydration of biotite. There is no evidence for the control of water activity by an external fluid reservoir. Limited amounts of water-undersaturated melts were extracted from their sites of generation. This process was responsible for the depletion of some leucosome assemblages with respect to K₂O, H₂O and in peraluminous rocks Na₂O. The partial melts were emplaced locally in developing shear zones.